UE Regulations On 5G Cybersecurity - Urszula SOLER (Communications of International Proceedings, 2021)
In recent years the 5th generation telecommunication technology has become a vital element of the race for the position of world economic leader. Because of the role that 5G can play in the economy the its technical capabilities, have become the subject of the "war for technology" between the two superpowers: China and the United States. As the consequences it became also part of the political debates all over the world. The European Union (EU) is aware of the fact that the position of Europe within the international arena depends to a large extent on how quickly European countries will develop and implement 5G technology. This article will try to answer on several question, e.g. What kind of support of research and development of 5G exist within the European Union? Which coordinating actions were undertaken by member states? How have different countries adopted the European Commission's plan to roll out 5G in the EU? The article will analyze, i.a. these issues in the policy context, presented in a broader perspective - the global geopolitical situation and the conflict between China and the United States. The study was conducted with the use of a critical analysis of state strategic documents, reports of institutions implementing and monitoring the development of 5G technology, as well as available literature on the subject and internet sources.
Keywords: cybersecurity; Europe; mobile networks; 5G technology